Impacts of pseudomonas fluorescent bacterial fertilizer addition on the soil environment and fruit yield under water stress in greenhouse grape - Gao, Yanting; Zhang, Hongjuan; Zhang, Rui; Huang, Zhen; Yang, Changyu (Frontiers in Microbiology, 2025)
Bacterial fertilizers, which contain beneficial soil microorganisms, are becoming more widely used as they can mitigate the problems of crop yields reduction and soil environment degradation caused by the overuse of chemical fertilizer. However, the impact of bacterial fertilizer on greenhouse grape yields and the rhizosphere soil environment has not been assessed in arid and semi-arid region of Northwest China. Thus, a 2-year field trial was conducted with five treatments: adequate water supply without bacterial fertilizer (CK); mild (W1), moderate (W2) water stress and small (F1), maximize (F2) fertilizer cross-combination, respectively. The results indicated that water stress had a negative impact on the accumulation of dissolved organic carbon (DOC), microbial biomass carbon (MBC), and microbial biomass nitrogen (MBN) in the rhizosphere soil. The addition of pseudomonas fluorescent bacterial fertilizer significantly increased the content of available phosphorus (AP), DOC, MBC and MBN content. The W1F2 treatment significantly increased the activities of urease, catalase and sucrase (p < 0.05). The W1F1 and W1F2 treatments increased fungal and bacterial diversity. Bacterial community composition was closely related to soil total organic carbon (TOC), soil organic matter (SOM), total nitrogen (TN), total phosphorus (TP), MBC, and sucrase, while fungi community composition was significantly related to Nitrate-N (NO3−-N), TN, and sucrase. Additionally, compared with CK treatment the yield and economic benefit of the W1F2 treatment increased by 35.44 and 44.04%, respectively. Therefore, W1F2 is recommended as the optimal water and fertilizer management scheme for efficient greenhouse grape production in the arid and semi-arid region of Northwest China.